Purple Class and the skelington : and other stories - Taylor, Sean, 1965-; Bate, Helen (London : Frances Lincoln Children's Books, 2006)
Contains four stories that follow the misadventures of Purple Class, including forgetful Jamal, rope-swinging Leon, Ivette, who is the best at everything, and other characters.
4.5
3-6
Keywords: Schools -- Juvenile fiction; Skeleton -- Juvenile fiction; Students -- Juvenile fiction; Schools -- Fiction; Skeleton -- Fiction; Students -- Fiction; School stories; Skeleton -- Fiction; Students -- Fiction